2019
DOI: 10.1111/1911-3846.12490
|View full text |Cite
|
Sign up to set email alerts
|

One Team or Two? Investigating Relationship Quality between Auditors and IT Specialists: Implications for Audit Team Identity and the Audit Process

Abstract: While prior research focuses on the audit team made up of auditors, we focus on the collective audit team made up of auditors and specialists—in our context, information technology (IT) specialists. Complex systems in today's audits and researcher and regulator concerns regarding ineffective coordination and communication between the two specializations motivate better understanding of this collective audit team. We investigate how auditors and IT specialists perceive their relationship and how the audit proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 104 publications
(248 reference statements)
1
44
2
2
Order By: Relevance
“…While more frequent interactions among auditors and forensic specialists are likely to result in some knowledge transfer, it is unclear whether, or to what extent, such interactions will lessen the cognitive authority of the specialists. In fact, our findings indicate that auditors largely accept and respect forensic specialists’ opinions; however, such attitudes stand in contrast with auditors’ attitudes toward IT and valuation specialists (Bauer and Estep ; Griffith ). Although we find evidence that auditors believe they are capable of performing a number of forensic‐like procedures, we do not find evidence that auditors actively seek to displace forensic specialists in the audit.…”
Section: Discussion and Future Researchcontrasting
confidence: 68%
See 1 more Smart Citation
“…While more frequent interactions among auditors and forensic specialists are likely to result in some knowledge transfer, it is unclear whether, or to what extent, such interactions will lessen the cognitive authority of the specialists. In fact, our findings indicate that auditors largely accept and respect forensic specialists’ opinions; however, such attitudes stand in contrast with auditors’ attitudes toward IT and valuation specialists (Bauer and Estep ; Griffith ). Although we find evidence that auditors believe they are capable of performing a number of forensic‐like procedures, we do not find evidence that auditors actively seek to displace forensic specialists in the audit.…”
Section: Discussion and Future Researchcontrasting
confidence: 68%
“…First, we asked which factors (e.g., clear understanding of forensic specialists’ role, timely involvement) contribute to the perceived successful integration of forensic specialists on one of their recent audits (Bauer and Estep ). Second, we asked participants which factors (e.g., a lack of a clear understanding of forensics’ role, a failure of timely involvement) contribute to a perceived lack of successful integration of forensic specialists on one of their recent audits (Bauer and Estep ). Prior research has identified challenges associated with specialist involvement on audits (Boritz et al.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout, we considered the degree to which incremental learning continued and whether we had reached saturation (Power and Gendron ; Malsch and Salterio ; Dai et al ). After completing 27 interviews, we concluded that interviewees no longer provided new information, and that saturation was reached (Griffith et al ; Hayne ; Bauer and Estep )…”
Section: Methodsmentioning
confidence: 99%
“…Of these specialists, the type most frequently used were those employed by audit firms (PCAOB 2015b). 5 Auditor-employed specialists are typically involved in supporting the financial statements audit on an ad hoc basis, during various phases, and often are not seen as part of the core audit team (e.g., Boritz et al 2015;Bauer and Estep 2016;Griffith 2016a). Consequently, the organizational structure of audit firms, differences in the timing when specialists are involved in the audit, and the fact that specialists are typically sourced from non-assurance groups, create conflicts between auditors and specialists that impede auditors' critical analysis and integration of the specialist's work (Boritz et al 2015).…”
Section: Auditor-specialist Interactions and The Specialist's Reportmentioning
confidence: 99%
“…Regulators and auditors identify these follow-up actions as important inputs to audit quality. Thus, this study provides the first evidence that adopting a specialist's perspective when auditors are at an expertise disadvantage has the potential to enhance auditor's judgments and decision-making and has implications for collaboration across geographically distributed and cross-functional teams.The PCAOB inspection reports, responses to the PCAOB's staff consultation paper on the use of specialists, and qualitative research on auditor-specialist interactions all indicate that auditors experience challenges critically evaluating and integrating the evidence provided by specialists (e.g., Bratten, Gaynor, McDaniel, Montague, and Sierra 2013;Boritz et al 2015; Harvest Investments 2015; PCAOB 2015b;Bauer and Estep 2016). There is limited empirical research, however, aimed at understanding possible causes for these challenges that auditors encounter, and potential strategies to improve auditors' critical evaluation and integration of the specialists' fieldwork and conclusions.…”
mentioning
confidence: 99%